2019
DOI: 10.1016/j.jaci.2019.06.019
|View full text |Cite|
|
Sign up to set email alerts
|

Cutaneous p38 mitogen-activated protein kinase activation triggers psoriatic dermatitis

Abstract: Background: Psoriasis is a chronic inflammatory skin disease characterized by IL-17-mediated immune responses. p38 is known to be highly activated in the psoriatic epidermis; however, whether p38 is involved in the development of psoriasis is unclear. Objective: We sought to demonstrate that activation of p38 mitogen-activated protein kinase is sufficient to induce psoriatic inflammation in mice and that cutaneous p38 activities are the topical therapeutic targets for psoriasis. Methods: A p38 activator, aniso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 49 publications
2
28
0
Order By: Relevance
“…Western blot analysis showed that phosphorylation of p38 in skin was induced after IMQ application (Fig 5, H), which is consistent with increased p38 phosphorylation in human psoriasis lesions. [36][37][38] In line with the results obtained with human keratinocytes, delivery of synthetic miR-149 suppressed IMQ-induced phosphorylation of p38 in mouse skin (Fig 5, H).…”
Section: Mir-149 Suppresses Tweak Signaling By Targeting Tweakrsupporting
confidence: 87%
“…Western blot analysis showed that phosphorylation of p38 in skin was induced after IMQ application (Fig 5, H), which is consistent with increased p38 phosphorylation in human psoriasis lesions. [36][37][38] In line with the results obtained with human keratinocytes, delivery of synthetic miR-149 suppressed IMQ-induced phosphorylation of p38 in mouse skin (Fig 5, H).…”
Section: Mir-149 Suppresses Tweak Signaling By Targeting Tweakrsupporting
confidence: 87%
“…Psoriasis is a recurrent, chronic skin disease with complex immune-inflammatory ethology (Nestle et al, 2009;Sakurai et al, 2019). The worldwide prevalence of psoriasis is about 3% and the high societal burden of this condition is mainly due to the substantial impact on the patients' perception of confidence and well-being (Lowes et al, 2007;Greb et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, in that study the characterization of the psoriasis phenotype was limited to evaluation of the histological features of the tissue at day 0 and 8. Others have also reported the use of ex vivo culture of psoriasis skin for testing effects of anti-inflammatory compounds [10,11]. However, in these studies characterization of the psoriasis phenotype upon ex vivo culture was not described and the culture time was shorter compared to our model, limiting the feasibility to investigate effects by anti-inflammatory compounds [10,11].…”
Section: Discussionmentioning
confidence: 94%
“…Others have also reported the use of ex vivo culture of psoriasis skin for testing effects of anti-inflammatory compounds [10,11]. However, in these studies characterization of the psoriasis phenotype upon ex vivo culture was not described and the culture time was shorter compared to our model, limiting the feasibility to investigate effects by anti-inflammatory compounds [10,11]. On the contrary, we demonstrated that the time frame in our model is sufficient to see treatment effects of both a small molecule and an antibody.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation